Effect of Trade Openness on Productivity in Cote d’Ivoire - Kouakou Germain Kramo (European Scientific Journal, ESJ, 2022)
The implementation of the African Continental Free Trade Zone offers important trade opportunities to African countries, including Côte d'Ivoire. The economic literature has shown that trade openness affects productivity. Therefore, this paper aims tocompare the effect of trade between Côte d'Ivoire and other African countries on productivity and the effect of trade between Côte d'Ivoire and the rest of the world (outside Africa) on productivity. To achieve this objective, the Dynamic Least Squares (DOLS) and Cointegration Canonical Regression (CCR) methods of Park (1992) were used to analyze the relationship between productivity and trade openness in Côte d'Ivoire over the period 1980-2019. We use Total Factor Productivity as measure of productivity in this study. The results show that the effect of trade between Côte d'Ivoire and African countries on productivity differs from the effect of trade between Côte d'Ivoire and the rest of the world (outside Africa) on productivity. Indeed, exports from Côte d'Ivoire to Africa have a positive and significant effect on productivity. while Côte d'Ivoire's imports from Africa have a negative and significant effect. Côte d'Ivoire's imports from the rest of the world (outside Africa) positively and significantly affect productivity. On the other hand, exports from Côte d'Ivoire to the rest of the world (outside Africa) have a negative and significant effect on productivity.